Multicomponent synthesis of spiropyrrolidine analogues derived from vinylindole/indazole by a 1,3-dipolar cycloaddition reaction - Narayanarao, Manjunatha; Koodlur, Lokesh; Revanasiddappa, Vijayakumar G.; Gopal, Subramanya; Kamila, Susmita (Beilstein Journal of Organic Chemistry, 2016)
A new series of spiropyrrolidine compounds containing indole/indazole moieties as side chains have been accomplished via a one-pot multicomponent synthesis. The method uses the 1,3-dipolar cycloaddition reaction between N-alkylvinylindole/indazole and azomethine ylides, prepared in situ from cyclic/acyclic amino acids. The 1,3-dipolar cycloaddition proceeds efficiently under thermal conditions to afford the regio- and stereospecific cyclic adducts.
Keywords: L-proline; ninhydrin; sarcosine; spiropyrrolidine; 5-vinylindazole; 5-vinylindole